Web Application Based Assessment and Ranking Development Model in Rock Climbing - PAMBAYUN, DANDI GALANG; Rahayu, Tandiyo; Kusuma, Donny Wira Yudha (Journal of Physical Education and Sports, 2021)
In this research, the scoring and rating system requires the use of effective and efficient technology. The problem in this research is that the scoring and ranking system is still done manually using Microsoft Excel. In addition, it was found that the scoring and ranking system was less open.This study aims to determine the assessment and ranking model based on software suitable for rock climbing, the feasibility of developing a web application-based assessment and ranking software development model, the effect of using a web application-based software development model developed. This study uses the Research and Development (R & D) method. The research location is in the Indonesian Rock Climbing Federation (FTPI) in Lamongan Regency. The research subjects were coaches, athletes, officials, and spectators. The product developed is a web application-based scoring and ranking software development model on rock climbing which has been validated by 3 experts, 3 practitioners, and 2 users. The operational field test of the developed model used a one-group pretest-posttest design. Seen from the average value of the pretest was 55.33 and posttest was 84.50 has increased.So it can be concluded as follows that the assessment and ranking model in rock climbing used is still manual and conventional, the model developed is feasible for users in rock climbing sports, modeldeveloped can increase user knowledge. The conclusion is that the mechanism for the use of web applications based on can effectively improve user knowledge in conducting assessments and rankings in rock climbing.